Essential role of amino acid position 226 in oligosaccharide elongation by amylosucrase from Neisseria polysaccharea. Issue 9 (6th May 2014) - Cambon, Emmanuelle; Barbe, Sophie; Pizzut‐Serin, Sandra; Remaud‐Simeon, Magali; André, Isabelle
ABSTRACT Amylosucrase from Neisseria polysaccharea is a remarkable transglucosylase that synthesizes an insoluble amylose‐like polymer from sole substrate sucrose. One particular amino acid, Arg226, was proposed from molecular modeling studies to play an important role in the formation of the active site topology and in the accessibility of ligands to the catalytic site. The systematic mutation of this Arg residue by all 19 other possible amino acids revealed that all single‐mutants had a higher activity on sucrose compared to the wild‐type enzyme. An extensive kinetic investigation showed that catalytic efficiencies are greatly impacted by the presence of natural acceptors in the reaction media, their chain length and the nature of the amino acid at position 226. Compared to the wild‐type enzyme, the R226N mutant showed a 10‐fold enhancement in the catalytic efficiency and a nearly twofold higher production of an insoluble amylose‐like polymer that can be of interest for biotechnological applications. Biotechnol. Bioeng. 2014;111: 1719–1728. © 2014 Wiley Periodicals, Inc.